An analysis of the effects of labor productivity on the adoption of product and process innovation among ASEAN manufacturing firms - Bermejo, Nina Gabrielle B. (Animo Repository, 2021)
Innovation, defined as being able to produce a new or improved process/product which has a significant difference from the previous and has been made available for use, has been crucial to economic growth and development, especially for emerging markets like those from the Association of Southeast Asian Nations (ASEAN). Additionally, firms engaging in innovation allow them to maximize the latest information and technology and gain a competitive advantage in the local and global markets. However, the firms from countries belonging to the ASEAN region may be more hesitant to this shift towards innovating, as the manufacturing firms in these economies are more labor-intensive. With this, the paper aims to establish and measure the effects of labor productivity on firms’ decisions to invest in product and process innovation in select ASEAN countries using firm-level data from the World Bank Enterprise Survey. Additionally, other firm characteristics will be considered in determining their effects on firm innovation. The researchers hypothesize that labor productivity would positively affect the firms’ decision in investing in product and process innovation.